Características vegetativas de pereiras enxertadas sobre marmeleiro e Pyrus calleryana. - Francescatto, Poliana (2009)
Quince has been used as an alternative of rootstock for pear trees because of its dwarfing effect which allows better tree vigor control, fruiting precocity and yield influence. However, highlighting the issue of rootstock versus cultivar, some combinations show severe problems regarding graft incompatibility. The main characteristics seen by incompatible combinations are cell necrosis and vascular discontinuity at the graft interface, leading to a rupture of the union or a slow tree decline. Therefore, the study aimed to evaluate the influence of different quince and Pyrus calleryana on vegetative growth of pear trees through combination performance, scion x rootstock. The work was carried out at the Centro Agropecuário da Palma in Capão do Leão, RS, from March 2007 to March 2009. The assessed cultivars were Carrick, Packham s Triumph and Williams, and the rootstocks were: P. calleryana and the quinces Adams, Alaranjado, Alongado, BA29, Berreckzi, Champion, D Angers, D Vranja, De Patras, Du Lot, Inta267, MC, Meliforme, Pineapple, Portugal and Smyrna. Tree height, increment of tree height; canopy volume; rootstock, union and scion diameters; diameters increment of rootstock, union and scion; fresh pruning weight and specific leaf area. The rootstock P. calleryana showed superior vigor for the three cultivars whether compared with all evaluated quince rootstocks. Incompatibility between plants is not individually defined only by the overgrowth at the graft union. Both observation and comparison of the all tree characteristics due scion/rootstock combination is of fundamental importance to diagnose incompatibility. Tree height, canopy volume and fresh pruning weight are the representative variables of pear tree vigor. The cultivar Carrick showed reduced vigor (64% in relation to P. calleryana) and compatibility with the quince rootstocks (in descending order of vigor): ‗Inta267 , ‗D Vranja , ‗BA29 , ‗Champion , ‗Portugal , ‗Pineapple , ‗Adams , ‗MC , ‗Berreckzi and ‗Meliforme . ‗Alaranjado and ‗Du Lot were incompatible with this cultivar. The cultivar Packham s showed reduced vigor (46.5% in relation to P. calleryana) and compatibility with the quince rootstocks (in descending order of vigor): ‗Smyrna , ‗D Angers and ‗Alongado . ‗Adams was incompatible with this cultivar. The cultivar Williams showed reduced vigor (60.4% in relation to P. calleryana) and compatibility only with the quince rootstocks (in descending order of vigor): 'Champion , ‗Meliforme and 'Du Lot . ‗BA29 , 'Smyrna , ‗Berreckzi , 'D Vranja , ‗De Patras and ‗MC were incompatible with this cultivar.